Strumma ovarii: a case report and literature review - Oswaldo, Rodríguez-Juárez Irving; Jose, Moreno-Peña Pablo; Amado, Méndez-Pérez Alan; Andres, Avalos-Bishop; Christian Enrique, Soule-Martinez (International Surgery Journal, 2022)
Struma ovarii is an uncommon monodermic teratoma in which thyroid tissue is the predominant element. Its low prevalence, wide age of presentation, variable clinical manifestations, and the lack of accurate diagnostic methods, contribute to the overall high percentage of misdiagnosis (90%). Surgery is the best available therapeutic option and the prognosis in most cases is good. This article summarizes the most relevant points for the diagnosis, management, and follow-up of this pathology.